Bimodular high temperature planar oxygen gas sensor - Sun, Xiangcheng; Liu, Yixin; Gao, Haiyong; Gao, Pu-Xian; Lei, Yu (Frontiers in Chemistry, 2014)
A bimodular planar O2 sensor was fabricated using NiO nanoparticles (NPs) thin film coated yttria-stabilized zirconia (YSZ) substrate. The thin film was prepared by radio frequency (r.f.) magnetron sputtering of NiO on YSZ substrate, followed by high temperature sintering. The surface morphology of NiO nanoparticles film was characterized by atomic force microscopy (AFM) and scanning electron microscopy (SEM). X-ray diffraction (XRD) patterns of NiO NPs thin film before and after high temperature O2 sensing demonstrated that the sensing material possesses a good chemical and structure stability. The oxygen detection experiments were performed at 500 °C, 600 °C and 800 °C using the as-prepared bimodular O2 sensor under both potentiometric and resistance modules. For the potentiometric module, a linear relationship between electromotive force (EMF) output of the sensor and the logarithm of O2 concentration was observed at each operating temperature, following the Nernst law. For the resistance module, the logarithm of electrical conductivity was proportional to the logarithm of oxygen concentration at each operating temperature, in good agreement with literature report. In addition, this bimodular sensor shows sensitive, reproducible and reversible response to oxygen under both sensing modules. Integration of two sensing modules into one sensor could greatly enrich the information output and would open a new venue in the development of high temperature gas sensors.